Poljska primerjalna književnost - stanje in perspektive - Zelenka, Miloš (Primerjalna književnost, 2011)
The paper examines the current state and prospects of Polish comparative studies after 1989. Although the first department of comparative literature in Central Eastern Europe was established at Warsaw University in 1818, after the Second World War comparative studies vanished altogether from the local curricula and scholarly pursuits. In the last twenty years this situation has changed.
Keywords: comparative literature; primerjalna književnost; Poland; Poljska; poljska literarna veda